Content and language integrated learning - Coyle, Do 1952-; Hood, Philip 1951-; Marsh, David 1956- (Cambridge University Press, 2010)
"CLIL (Content and Language Integrated Learning) has emerged since the millennium as a major trend in education. Written by Do Coyle, Philip Hood and David Marsh and drawing on their experience of CLIL in secondary schools, primary schools and English language schools across Europe, this book gives a comprehensive overview of CLIL. It summarises the theory which underpins the teaching of a content subject through another language and discusses its practical application, outlining the key directions for the development of research and practice. This book acknowledges the uncertainty many teachers feel about CLIL, because of the requirement for both language and subject knowledge, while providing theoretical and practical routes towards successful practice for all"--Provided by publisher
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Sprache; Education, Bilingual -- Europe; Language and languages -- Study and teaching -- Europe; Language arts -- Correlation with content subjects -- Europe; Content and language integrated learning; Zweisprachiger Unterricht; Europa